The Influence of Land Use Change and Spatial Discretization of Middle - Lower Ciliwung Sub-Watershed on Flood Hydrograph at Manggarai Weir : a Preliminary Study - Eko Wahyuning Tiyas, Nonik; Sutjiningsih, Dwita (International Journal of Engineering and Technology, 2018)
Jakarta is a lowland area with 40% of its territory at an elevation below the sea level so it is very vulnerable to flooding. One of out many causes floods in Jakarta is by the overflow of the Ciliwung River. The Ciliwung Watershed has a very strategic value in Indonesia because the Ciliwung River is one of thirteen rivers crossing the nation's capital. The rapid urbanization and population growth led to an increasing impervious area in the Ciliwung Watershed which resulted in a flood hydrograph change. This research aims to determine the influence of land use change, which is taking into account the spatial discretization and the riparian characteristic of Middle - Lower Ciliwung Sub-Watershed on flood hydrograph at Manggarai Weir. This research reviews the related literature on the implementation of HEC-GeoHMS version 10.1 developed by US Army Corps of Engineers (2013) to estimate the effect of land use change on flood hydrographs by taking into account the characteristics of the riparian described descriptively and present arguments to claim that the discretization spatial method can provide significantly more flood hydrographs results with existing conditions.Â Â